The Relationship Between Iron Accumulation, Vitamin D Deficiency and Bone Mineral Density in Patients with Thalassemia Major, Thalassemia Intermedia and Sickle Cell - Mahmut Büyükşimşek; İsmail Fikri Başlamışlı (Galenos Yayinevi, 2020)
Objective:Osteopenia and osteoporosis are important causes of morbidity in patients with hemoglobinopathies. This study investigates the association between iron accumulation, vitamin D and bone mineral density (BMD) in patients with thalassemia major, thalassemia intermedia and sickle cell.Materials and Methods:Serum samples collected from 102 patients with hemoglobinopathy were used; the relationship between ferritin, vitamin D levels and BMD, which was performed with dual energy X-ray absorptiometry (DEXA), was investigated.Results:The ratio of thalassemia intermedia, thalassemia major and sickle cell patients with normal BMD according to the DEXA Femoral T-score was 56.25%, 35% and 39%, respectively. The ratio of thalassemia intermedia, thalassemia major and sickle cell patients with normal BMD according to the DEXA lumbar T-score was 31.25%, 7.5% and 41.25%, respectively. When the patients' ferritin values and DEXA scores were compared, femur T-score, lumbar T-score, femur Z-score and lumbar Z-score were significantly lower in those with high ferritin values (p values were respectively: 0.0005, 0.0002, <0.0001, 0.0002). When the femur T-score, lumbar T-score, femur Z-score and lumbar Z-score were compared in patients with normal and low vitamin D levels, a statistically significant change was observed in the severe deficiency patients (p values were respectively: 0.001, 0.001, 0.0027, 0.0003).Conclusion:Patients with hemoglobinopathy should be screened through DEXA at an early age. The efforts to provide appropriate vitamin D replacement and to restore the ferritin levels to the normal range may be effective in reducing the morbidity associated with osteoporosis.